Effect of Bone Marrow Mesenchymal Stromal Cell Therapies in Rodent Models of Sepsis: A Meta-Analysis - Ge, Lite; Zhao, Jing; Deng, Huiyin; Chen, Chunli; Hu, Zhiping; Zeng, Liuwang (Frontiers in Immunology, 2022)
ABSTRACT Background: Multiple preclinical studies have demonstrated that bone‐marrow derived mesenchymal stromal (stem) cells (MSC(M)) positively influence the severity of sepsis symptoms and mortality in rodent models. However, this remains an inconclusive finding. Objective: To review the effect of naïve MSC(M) in rodent models of sepsis. Methods: The PubMed, EMBASE, and Web of Science databases were searched up to August 31, 2021. Inclusion criteria according to PICOS criteria were as follows: (1) population: rodents; (2) intervention: unmodified MSC(M); (3) comparison: not specified; (4) primary outcome: the effects of MSC(M) cell therapy on the mortality of rodent models of sepsis and endotoxemia; (5) study: experimental studies. Multiple prespecified subgroup and meta-regression analysis were conducted. Following quality assessment, random effects models were used for this meta-analysis.The inverse variance method of the fixed effects model was used to calculate the pooled odds ratios (ORs) and their 95% confidence intervals (CIs). Results: twenty-four animal studies met the inclusion criteria. Our results revealed an overall OR difference between animals treated with naïve MSC(M) and controls for mortality rate was 0.34(95% confidence interval: 0.27-0.44; P < 0.0001) . Significant heterogeneity among studies was observed. Conclusions: The findings of this meta-analysis suggest that naïve MSC(M) therapy decreased mortality in rodent models of sepsis. Additionally, we identified several key knowledge gaps, including the lack of large animal studies and uncertainty regarding the optimal dose of MSC(M) transplantation in sepsis. Before MSC(M) treatment can advance to clinical trials, these knowledge gaps must be addressed.